MYC—an emerging player in mitochondrial diseases - Purhonen, Janne; Klefström, Juha; Kallijärvi, Jukka (Frontiers in Cell and Developmental Biology, 2023)
The mitochondrion is a major hub of cellular metabolism and involved directly or indirectly in almost all biological processes of the cell. In mitochondrial diseases, compromised respiratory electron transfer and oxidative phosphorylation (OXPHOS) lead to compensatory rewiring of metabolism with resemblance to the Warburg-like metabolic state of cancer cells. The transcription factor MYC (or c-MYC) is a major regulator of metabolic rewiring in cancer, stimulating glycolysis, nucleotide biosynthesis, and glutamine utilization, which are known or predicted to be affected also in mitochondrial diseases. Albeit not widely acknowledged thus far, several cell and mouse models of mitochondrial disease show upregulation of MYC and/or its typical transcriptional signatures. Moreover, gene expression and metabolite-level changes associated with mitochondrial integrated stress response (mt-ISR) show remarkable overlap with those of MYC overexpression. In addition to being a metabolic regulator, MYC promotes cellular proliferation and modifies the cell cycle kinetics and, especially at high expression levels, promotes replication stress and genomic instability, and sensitizes cells to apoptosis. Because cell proliferation requires energy and doubling of the cellular biomass, replicating cells should be particularly sensitive to defective OXPHOS. On the other hand, OXPHOS-defective replicating cells are predicted to be especially vulnerable to high levels of MYC as it facilitates evasion of metabolic checkpoints and accelerates cell cycle progression. Indeed, a few recent studies demonstrate cell cycle defects and nuclear DNA damage in OXPHOS deficiency. Here, we give an overview of key mitochondria-dependent metabolic pathways known to be regulated by This is a provisional file, not the final typeset article MYC, review the current literature on MYC expression in mitochondrial diseases, and speculate how its upregulation may be triggered by OXPHOS deficiency and what implications this has for the pathogenesis of these diseases. Figure 1. The cartoon illustrates some central physiological processes in mammalian cells and tissues to which MYC-regulated transcriptional programs contribute as driver, modulator, or adaptor. The abbreviation mt-ISR stands for mitochondrial integrated stress response. See sections 3-5 in the main text for elaboration.